Isolation of a coronavirus during studies on puffinosis, a disease of the Manx shearwater (Puffinus puffinus) - Nuttall, P A; Harrap, K A (Archives of virology, 1982)
A virus was isolated from 2 day-old mice inoculated with homogenates of either the lungs or blood of 2 different shearwaters affected by puffinosis. Examination of infected suckling mouse brain and infected NCTC-1469 (mouse liver) cell cultures, by electron microscopy, revealed virus particles and inclusion bodies characteristic of a coronavirus. Neutralization, complement fixation and fluorescent antibody tests showed that the virus was related to mouse hepatitis virus. The virus was not isolated from 445 control, uninfected mice. Neutralising antibodies were not detected in 39 sera from diseased shearwaters and 2 sera from apparently healthy birds. Two shearwaters inoculated with the virus did not develop clinical signs of infection. The question of whether the virus was isolated from shearwaters or from laboratory mice is discussed.